The bargaining trap - Sebastian Schweighofer-Kodritsch (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
I revisit the Rubinstein (1982) model for the classic problem of price hag- gling and show that bargaining can become a 'trap,' where equilibrium leaves one party strictly worse off than if no transaction took place (e.g., the equilibrium price exceeds a buyer's valuation). This arises when one party is impatient about capturing zero surplus (e.g., Rubinstein's example of fixed bargaining costs). Augmenting the protocol with unilateral exit options for responding bargainers generally removes the trap.
Keywords: C78; D03; D74; 330; alternating offers; bargaining; time preferences; haggling costs; outside options